EKPLORASI PENGOLAHAN SERAT SABUT KELAPA DENGAN PEWARNA ALAMI SECANG SEBAGAI MATERIAL ALTERNATIF FURNITUR - Ade Putri, Sindi; Fitra Andriana, Yunita; Septiana, Ulfa (IKRA-ITH Teknologi Jurnal Sains dan Teknologi, 2019)
Indonesia is one of the countries in the world that produces highest amount of coconut. In a year, the amount of coconut fiber produced in Indonesia reached 18 million tons, but its utilization has been done less than 5%. Even though the enormous amount of its production and its strong character havea high potential to be processed into more useful alternative materials, the utilization of coconut fiber is still limited in furniture and handicraft industries. Theexploration of coconut fiber as an alternative material was aimed to producing natural raw materials that are environmentally friendly and supporting the idea of using coconut fiber into products that have high economic value. In addition, coloring process with sappan wood extraction has been conducted in this study in aim toelevatecoconut fiber aesthetic value. The method used in this study is descriptive experimental. In theapproaching process, several explorations were conducted to find the right technique in processing coconut fiber with the natural dye of sappan. Furthermore, after the exploration process has been conducted, the character of coconut fibers processed with resin has a strong character and good resistence by heat and water as well. It makes it suitable to be an alternative material for outdoor tables. In addition, the coloring exploration process of coconut fiber using sappan wood resulted color range from yellow to maroon.